Monetary cooperation between East & West - Zwass, Adam. (White Plains, N.Y. : International Arts and Sciences Press, 1975)
The book examine monetary and credit relations in Eastern Europe in the wake of the economic reforms. It also examine currency in the foreign trade of the CMEA nations and the general outlook for East-West monetary relations.
Translation of Zur Problematik der Währungsbeziehungen zwischen Ost und West.
Bibliography: p. 259-265.
usc17/10/18
Loans
Keywords: International finance; East-West trade; Foreign exchange